The issue lies in the fact that the original equation is 0=0.
Then, if you put in any value for x, you are dividing by 0 which as we all know, is a "no no."
2006-11-24 07:27:22
·
answer #1
·
answered by Anonymous
·
4⤊
2⤋
x = 0
2006-11-24 07:28:10
·
answer #2
·
answered by M00ND0CT0R 6
·
0⤊
0⤋
You divided by zero factor(x-x).And you know this simple fact x-x=0. Even at step 5 you have 2x-x=0 =>x=0
That is why basic properties like (additive/ commutative ) of numbers is important.
In step four, if you notice, you have placed 1 instead of 0/0 for (x-x)/(x-x).
Expression cancel out each other only when they do not present themselves as indeterminate like 0/0.
Basically numbers are just a concept and zero has a different status and aquite important one.
2006-11-24 07:50:38
·
answer #3
·
answered by balsmin 3
·
0⤊
0⤋
Step 3 is the problem. x - x = 0 for all x, and dividing by 0 is not defined. When you get down to step 6, "this is valid for any value of x" is not true.
2006-11-24 07:28:29
·
answer #4
·
answered by Philo 7
·
1⤊
0⤋
The problem is step 3, in which you divide both sides by (x - x). By definition, x - x = 0. Dividing by zero is an illegal procedure, punishable by a five-yard penalty.
2006-11-24 07:32:57
·
answer #5
·
answered by bgdddymtty 3
·
1⤊
0⤋
step 3 - x=0
2006-11-24 08:02:25
·
answer #6
·
answered by Xyoria 2
·
0⤊
0⤋
Step 3, you divided by zero.
2006-11-24 07:27:43
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
Step 3. More generally ab=ac if and only if b=c OR a=0. Here, you would get: 2x=x OR x=x: so there is no contradiction.
2006-11-24 07:36:42
·
answer #8
·
answered by chaps 2
·
1⤊
0⤋
Step 3 is where the error lies, because the equation is divided by (x-x) which is zero. You can't divide anything by zero, it's undefined.
2006-11-24 07:42:56
·
answer #9
·
answered by Nautilus 2
·
1⤊
0⤋
In step three you divide by zero (x-x). Everything after that is invalid.
2006-11-24 07:27:49
·
answer #10
·
answered by Berry K 4
·
0⤊
0⤋